Strength analysis of prestressed vertical cylindrical steel oil tanks under operational and dynamic loads - Tursunkululy, Timur; Zhangabay, Nurlan; Avramov, Konstantin; Chernobryvko, Maryna; Suleimenov, Ulanbator; Utelbayeva, Akmaral; Duissenbekov, Bolat; Aikozov, Yermurat; Dauitbek, Bakdaulet; Abdimanat, Zhuldyz (Eastern-European Journal of Enterprise Technologies, 2022)
This paper reports a study into the effect of the winding type on the stressed-strained state of the wall of a steel cylindrical tank filled with oil to the predefined level. The shapes of free oscillations of oil in the tank and the effect of the winding type on the natural frequencies of the structure were analyzed. Stress in the tank wall was estimated on the basis of finite-element simulation of the deformation of a three-dimensional structural model under the influence of distributed oil pressure on the inner surface of the wall and stresses on the outer surface of the wall. The stresses were induced by the winding of various types, taking into consideration the level of oil loading, the winding step of the winding, and the mechanical characteristics of the thread. The stressed-strained state of a cylindrical tank with winding was investigated at its full filling with oil, half-filling with oil, and without oil. Three winding options were simulated: single, double, and triple intervals. Two types of winding were considered: made from high-strength steel wire and made from composite thread. It was established that when winding the tank wall with steel wire at a triple interval, the stress in the structure does not exceed 34.2 % of the yield strength. At the same time, the height of oil loading does not significantly affect its strength. Applying a composite thread leads to an increase in the stress of up to 47.2 % of the yield strength but makes it possible to reduce the mass of the tank with winding. When winding with a composite thread at a triple interval, the mass of the structure increases by only 3.6 %. The results reported here make it possible to effectively use pre-stress in order to improve the strength and dynamic characteristics of the studied structures, taking into consideration their windings made of different materials